Agro-Climatic Bulletins: improving farmer decision-making through climate information services - Le Thi Tam; Nguyen, Huong Mai; Barlis, Angelica; Swaans, Cornelis P.M.; Trinh Thanh Ha (2022)
This animation video outlines the key steps in developing agro-climatic bulletins based on the field-tested approach introduced and piloted in the Mekong River Delta in Vietnam. This emphasizes the importance of local knowledge and expertise of the provincial and district stakeholders in developing tailored bulletins for farmers.